2020
DOI: 10.3390/pr8121681
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biofertilizers on Growth, Soil Fertility, and Nutrients Uptake of Oil Palm (Elaeis Guineensis) under Greenhouse Conditions

Abstract: The full dependency on chemical fertilizers in oil palm plantation poses an enormous threat to the ecosystem through the degradation of soil and water quality through leaching to the groundwater and contaminating the river. A greenhouse study was conducted to test the effect of combinations of biofertilizers with chemical fertilizer focusing on the soil fertility, nutrient uptake, and the growth performance of oil palms seedlings. Soils used were histosol, spodosol, oxisol, and ultisol. The three treatments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 58 publications
0
25
0
1
Order By: Relevance
“…These growthpromoting rhizobacteria can be categorized as (i) rhizhospheric, (ii) rhizoplane, (iii) endophytic and (iv) specific structural bacteria based on their connection with roots [31]. Direct mechanism of PGPR include biofertilization, root stimulation, rhizoremediation, and plant stress control, while antibiosis, induction of systemic resistance and competition for nutrients are the indirect mechanisms of PGPR [32]. It has been shown that, inoculation of beneficial bacteria are able to reduce the use of fertilizer and is a cost effective initiative in reducing the use of agrochemicals [33][34][35].…”
Section: Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…These growthpromoting rhizobacteria can be categorized as (i) rhizhospheric, (ii) rhizoplane, (iii) endophytic and (iv) specific structural bacteria based on their connection with roots [31]. Direct mechanism of PGPR include biofertilization, root stimulation, rhizoremediation, and plant stress control, while antibiosis, induction of systemic resistance and competition for nutrients are the indirect mechanisms of PGPR [32]. It has been shown that, inoculation of beneficial bacteria are able to reduce the use of fertilizer and is a cost effective initiative in reducing the use of agrochemicals [33][34][35].…”
Section: Bacteriamentioning
confidence: 99%
“…assist P solubilization and nutrient uptake in rice (Oryza sativa) and oil palm (Elaeis guineensis) [36]. Furthermore, inoculating rice with N 2 -fixing bacteria and P-solubilizing bacteria improves leaf chlorophyll content, plant nutrient absorption, and yield, and reduces N 2 and P fertilizer consumption by 50% [32]. In the absence of pathogen, rhizobacteria produce hormones such as gibberellic acid (GA), indole acetic acid (IAA), ethylene (ET) and cytokinins (CK), which helps in plant development.…”
Section: Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In return, the microorganisms benefit from the exudates and redox changes derived from the plants. Some of these microorganisms are biofertilizers (Ajeng et al, 2020) hence serve as biological plant growth-promoting agent, which enhances the rapid growth of plants suited for phytoremediation. Ruley et al…”
Section: Figure-1mentioning
confidence: 99%
“…In 2011, the FAO pointed out that approximately 175.5 million tons of chemical fertilizers were used in agriculture to achieve the best crop yield [6]. A large amount of chemical fertilizers are deposited in the soil, resulting in a decline in crop yield and quality, environmental damage, and soil pollution [7,8].…”
Section: Introductionmentioning
confidence: 99%